ADAPTIVE EDUCATIONAL TECHNOLOGIES: PRINCIPLES AND FOUNDATIONS (The Journal of Interdisciplinary Human Studies, 2026)
This article examines adaptive educational technologies as a transformative development in contemporary pedagogy. By integrating artificial intelligence, data analytics, and psychological insights, these systems construct individualized learning environments that respond dynamically to the needs of each student. Unlike traditional instructional models, adaptive technologies emphasize flexibility and inclusivity, ensuring that education remains both effective and equitable. The discussion highlights five foundational principles – personalization, real-time feedback, engagement, inclusivity, and continuous improvement – demonstrating how they collectively enhance motivation, reduce stress, and foster sustainable learner-centered outcomes.
Keywords: adaptive learning; personalized education; educational technology; real-time feedback; adaptive testing; student engagement; motivation in learning